Is the DCFTA Between EU and Ukraine Negatively Impacting Russia's Economy? - Ion Pohoata; Aida-Loredana Baciu; Paula-Alexandra Roibu (CES Working Papers, 2016)
This paper aims to highlight specific aspects and consequences of the dual nature of relations between Russia and Ukraine in the context of DCFTA's implementation. We are interested to encounter the point of contact and the interference areas to which Ukraine is referring to secure its balance, considering that its economy and market are traditionally oriented toward Russia and DCFTA is reorienting it toward EU and in this context, to show that the Russian economy is not, fundamentally, affected. Based on the statistical data that provides the economic situation of the two countries (import, export, FDI, labour migrants) before and after signing the treaty, we will analse the manner in which DCFTA affects the Russian economy. The findings indicate that that the implementation of the DCFTA does not have the potential to cause instability in trade relations between Ukraine and Russia, and that, precisely, the hostile actions of Russia against the DCFTA has jeopardized the country's position on economic actors arena.
Keywords: F51; F5; 330; DCFTA; Ukraine; Russia; trade; economic consequences; sanctions